Johann Zoffany, Classical Art, Italy and Russian Patronage: Shedding New Light on Models, Men and Paintings - Ambrosini Massari, Anna Maria (Actual Problems of Theory and History of Art, 2015)
Johann Zoffany’s famous painting of the Tribuna of the Uffizi (Royal Collections, UK) does not portray that room as it was, but sums up a number of classical models of paramount importance in the artistic and social education of any well-bred person in eighteenth-century Europe. This German artist, long active in Hannoverian Britain, provides opportunities of appreciating how classical art inspired European collectors, such as in Charles Townley’s Library (Burnley, Townley Hall Art Gallery and Museum). Nevertheless, the Tribuna undoubtedly provides a perfect list of essential models with a reference to the international, lively circle gathered around Zoffany in Florence when he was working at his Tribuna, from 1773 to 1777. The paper sheds new light on a less known episode which deserves greater attention. It concerns the portraits painted by Zoffany for two very important Russian grandees: the Orlov brothers, namely Prince Grigorii, who had been Catherine the Great’s favourite, and Count Aleksei. It was most probably through one of the Orlovs that the Empress heard of the Tribuna, a painting that according to some sources she tried to obtain for her prominent collection at the Hermitage. Zoffany’s portraits of the Orlovs are as yet untraced, but the paper offers reconstruction of their complete story based on notable written sources, some copies and derivations and other connected works. This reconstruction opens up the author’s view on contemporary continental art-market and the cultural exchanges between Italy and Russia, with special focus on classical art. It might also help to retrieve the original portraits of the Orlovs, which probably hang still unacknowledged somewhere in Russia.
Keywords: Zoffany; Classical art; Italy art; Britain; Russia